2001
DOI: 10.1524/ract.2001.89.10.653
|View full text |Cite
|
Sign up to set email alerts
|

Interaction study between Ca2+ and humic acids in brine media

Abstract: Humics / Ca(II) / Brine / Stability constants / Ternary complexSummary. The interaction between Ca 2+ and humic acids (HA) was studied at ionic strengths from 0.10 to 5.0 m (NaCl) by the solvent extraction technique. The dependence of the stability constants upon pcH (4.7 to 9.0) was interpreted by the polyelectrolyte model of HA. The data was consistent with formation of a single Ca-HA complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Although proton titrations of HA are rarely carried out for I > 1 m, a number of critical studies do exist. Kurk and Choppin (2000) and Laszak and Choppin (2001) performed proton titrations of HA at I = 0.1, 0.3, 1, 3 and 5 m (NaCl), and calculated apparent dissociation constants (pK a ) for HA considering two acidic groups. They found that pK a variation was insignificant (±0.1) within this range of ionic strengths.…”
Section: Proton Titration In Saline Solutionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although proton titrations of HA are rarely carried out for I > 1 m, a number of critical studies do exist. Kurk and Choppin (2000) and Laszak and Choppin (2001) performed proton titrations of HA at I = 0.1, 0.3, 1, 3 and 5 m (NaCl), and calculated apparent dissociation constants (pK a ) for HA considering two acidic groups. They found that pK a variation was insignificant (±0.1) within this range of ionic strengths.…”
Section: Proton Titration In Saline Solutionsmentioning
confidence: 99%
“…In a number of laboratory studies, Choppin and co-workers (Labonne- Wall et al, 1999;Kurk and Choppin, 2000;Laszak and Choppin, 2001;Wall et al, 2002) to metal ions and must therefore be taken into account in the calculations (Labonne-Wall et al, 1999;Wall et al, 2002). Finally, unlike the other cations, for pH m ≈ 5 under ambient (air) atmosphere, UO 2 2+ hydrolysis and complexation by carbonate anions cannot be neglected (Langmuir, 1978;Labonne-Wall et al, 1999 and Ni 2+ ) and Laszak and Choppin (2001)…”
Section: Cation-ha Complexation In Nacl Solutionsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the systems where Ca 2 + interacts with humic acid, one of the naturallyoccurring organic substances, the slope of the log K d vs. pH plots is reported to get smaller with an increase of NaCl concentrations. 13) 1.00…”
Section: Subtiusmentioning
confidence: 99%